A Study On the Mechanical Properties of Pla, Abs and Petg Filament Printed by Various Type of Infill Design Using 3d Printing Machine - Sa'ude, Nasuha; Ab Latib, Nur Anis Nabilah (Research Progress in Mechanical and Manufacturing Engineering, 2024)
3D printing is the process of turning digital models into physical objects through layer-wise material deposition or hardening. The basic technique of 3D printing is to build a product layer by layer by adding or printing material. The mechanical properties of PLA, ABS and PETG filament printed using a 3D printer with various types of infill and different type of infill percentage such as line and hexagon, 50% and 100% infill are studied in this research in this study. Mechanical properties vary depending on the type of infill pattern and its percentage used. Tensile, flexural, and impact tests were performed as part of the mechanical analysis. The specimens are printed using a dog bone model created with Solidworks software and printing by Ender 3Pro, 3D printer. Based on the results obtained from tensile test, the PLA material, hexagon type of infill with 100% percentage of infill shows the highest tensile strength and modulus elasticity where the value recorded was 49.82 MPa and 7.56 MPa.  Followed by PETG material, where the tensile strength and modulus elasticity value were 49.05 MPa and 5.31 MPa respectively. The lowest tensile strength was ABS material, where the tensile strength and the modulus elasticity value were 27.55 MPa and 4.89 MPa. As for the flexural strength and modulus, PLA material, the hexagon type of infill with 100% infill was recorded the highest where the values were 101.02 MPa and 29.60 MPa. Followed by the ABS material, where the flexural strength and modulus value were 83.67 MPa and 23.14 MPa respectively. The lowest flexural strength was PETG material, where the flexural strength and the modulus value were 72.54 MPa and 21.59 MPa. Next, for impact test, ABS material, hexagon type of infill with 100% of infill was the highest for impact strength where the result recorded was 1.136J/mm².  Followed by PLA material, where the impact strength was 0.226 J/mm². The lowest tensile strength was PETG material, where the impact strength value was 021 J/mm². In conclusion, it can be concluded that hexagon type with 100% infill was the best compared to line type of infill as it shows the highest result for all mechanical test conducted.